2010
DOI: 10.1111/j.1540-6210.2010.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Barriers to Cooperation: Intergovernmental Service Agreements

Abstract: Interlocal cooperation through service-sharing agreements has a long history, but its use has increased in popularity during the last 20 years. Th e decisions of local government units to collaborate through intergovernmental service agreements are best understood as a two-stage process. Th e fi rst stage, in which communities decide whether to consider interlocal cooperation, involves the nature of the immediate problem faced plus specifi c demands for performance and effi ciency gains that can result from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 35 publications
5
109
1
1
Order By: Relevance
“…The results were shown that the antecedents are positively correlated with trust, and trust is positively correlated with network performance. The result is consistent with Kwon and Feiock (2010). They studied coservices networking in local government organizations.…”
Section: Antecedentssupporting
confidence: 78%
“…The results were shown that the antecedents are positively correlated with trust, and trust is positively correlated with network performance. The result is consistent with Kwon and Feiock (2010). They studied coservices networking in local government organizations.…”
Section: Antecedentssupporting
confidence: 78%
“…Selama ini dalam menjalankan aktivitasnya lembaga ini hanya mengandalkan dana iuran dari kabupatan anggota. (Kwon dan Feiock, 2010).…”
Section: Sumber Pendanaanunclassified
“…Because of their role in delivering identical or at least similar services to citizens and companies, public administrations often cooperate to leverage synergies and improve efficiency, with many administrations sharing the responsibility for service delivery and collectively providing services (Bel and Warner, 2015;Kwon and Feiock, 2010;Leroux and Carr, 2007;Wood, 2006). The concepts of shared service centers and shared service networks have emerged as a way to optimize the execution of the internal governmental processes involved in providing services (Niehaves and Krause, 2010;Paagman et al, 2015).…”
Section: Cooperation and Standardization In Governmental Institutionsmentioning
confidence: 99%